Associação das concentrações séricas de testosterona com o consumo de colesterol e com a força muscular de homens - Gomes, Gederson Kardec (2022)
Testosterone is an anabolic androgenic steroid hormone synthesized from cholesterol, it is considered an important hormone for the structure and function of skeletal muscle. However, little is known about the relationship between cholesterol intake and serum testosterone concentrations, and the relationship between serum testosterone concentrations and muscle strength in men. Aim: 1) to assess whether cholesterol intake and serum total cholesterol levels are associated with serum total testosterone concentrations in men; 2) to investigate whether serum concentrations of total testosterone are associated with handgrip strength in men. Methods: The studies are cross-sectional, and the participants are men aged 20 to 80 years from the National Health and Nutrition Examination Survey (NHANES). In study 1, the 2013-2014 biennium (n=1996) was used. We evaluated the association between cholesterol intake (through two 24-hour dietary recalls) and serious total cholesterol levels with serum total testosterone concentrations. Linear regression analysis was performed to see whether serum total testosterone concentrations are associated with cholesterol intake and serum total cholesterol levels. In study 2, the 2011-2012 biennium (n=2049) was used, and the association between serum concentrations of total testosterone and the sum of handgrip strength (sum of right-hand and left-hand strength) was evaluated. Linear regression analysis was performed to observe whether serum levels of total testosterone are associated with the sum of handgrip strength, in men aged 20 to 80 years and separated by age, young man (20 to 39 years); middle-age (40 to 59 years) and older man (60 to 80 years). Results: In study 1, cholesterol intake and serum total cholesterol levels were not associated with serum total testosterone concentrations in unadjusted and adjusted analyzes (adjusting for energy intake, total fat and alcohol, smoking, age, activity physical activity, family income, marital status, race, education, diabetes, hypertension and body mass index). In study 2, we observed positive associations (p<0.001) between serum total testosterone concentrations and the sum of handgrip strength in the adjusted model (adjusting for energy and alcohol intake, smoking, age, physical activity, family income, marital status, race, education, diabetes, hypertension, arthritis and body mass index). When we separated the participants by age-range, we found positive associations between serum total testosterone concentrations and the sum of handgrip strength in the adjusted model in individuals between 20 and 39 years old (p<0.001) and between 40 and 59 years old (p=0.036). Conclusion: We conclude that cholesterol intake and serum cholesterol levels are not associated with serum total testosterone concentrations. Serum total testosterone concentrations show positive associations in young and middle-aged men, but not in older men.